E-commerce in Turkey - Stefaniuk, Tomasz; Çalişkan, Betül (Management and Administration Journal, 2019)
E-commerce (electronic commerce), although it is a relatively young branch of the economy, has caused that more and more business processes are transferred to the Internet. The dynamic development of e-commerce is evidenced by the several-dozen-percent increase in its users every year. The article presents the outline of the e-commerce market in Turkey. It presents the essence of E-commerce, the history of its development in Turkey and the current state of e-commerce in this country, in comparison with other countries. Attention was also paid to conditions that create good prospects for its growth.